The Influence of Foundation Bodies in The Teaching of Religious Education in Selected Primary Schools in Kasagama Sub-County Lyantonde District. - Kafeero, Athanus (Kabale University, 2023)
he study was done in five selected primary schools in Kasagama Sub-county Lyantonde District. The purpose of the study was to investigate on the influences of the foundation bodies in the teaching of religious education in primary schools in Kasagama Sub-county Lyantonde District. The study objectives were; to find out the influence of foundation bodies in the teaching of religious education in primary schools, to investigate why foundation bodies in the teaching of religious education in primary schools. The study was carried out in five randomly selected Primary Schools in Kasagama Sub-county. A total number of 175 out of 340 respondents were selected to participate in the study. The target population were pupils, teachers, Headteachers and peasants. The researcher used questionnaires and interview guides in collecting the necessary data about the subject. The data collected was analyzed using both qualitative and quantitative techniques and presented in tables in forms of frequencies and percentages. The study revealed that; there were influences of foundation bodies in the teaching of religious education in primary schools and these included encouraging to grow up following the cultures and beliefs of their religion. encouraging pupils to have good manners and putting God first in their academics'. There were reasons why foundation bodies tended to influence in the teaching of religious education in Primary Schools and these included encouraging good morals among pupils, encouraging them to concentrate in their studies and putting God first in their academies. There were possible measures to improve on the teaching of religious education in primary schools: These included self-teaching exercises, individual pupil attention and community participation in school activities both in academic and non-academic activities. The recommendations made by the researcher were; the foundation bodies should have an influence in the teaching of religious education in primary schools. Foundation bodies tended to influence the teaching of religious education in primary schools. Teachers should use better methods of teaching such as guided discovery. presentation, discussion and demonstration. Areas for further study will be about the causes of pupils’ poor performance in religious education in primary schools.